Republic of Uzbekistan : Technical Assistance Report-Monetary and Financial Statistics Mission (July 17-August 2, 2019). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
This technical assistance report on the Republic of Uzbekistan states that the mission achieved all its objectives and Uzbekistan's country page is now ready to be introduced in International Financial Statistics. Uzbekistan has recently intensified its efforts to improve its financial sector statistics. With the ongoing liberalization of the Uzbek economy, availability of granular data for an assessment of risks related to the financial sector is becoming more important. Uzbekistan reports 11 core and one additional financial soundness indicators (FSI) for deposit takers on a quarterly basis for publication on the IMF's website. The one important improvement needed, particularly for the other depository corporation survey, is the enhancement of the counterparty sector classifications. The mission also assisted the Central Bank of Uzbekistan in establishing an initial framework for the compilation of a quarterly other financial corporation survey using the Standardized Report form 4SR. The Prudential Supervision Department is now ready to report all core and additional FSIs for deposit takers (DT), as well as their underlying financial statements, with the reporting frequency to be increased from quarterly to monthly. In order to support progress in the several areas, the mission recommended a detailed action plan with the priority recommendations summarized.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet